Retinal Sensitivity in Patients with Type I Diabetes without Retinopathy or with Minor Retinal Changes - Pinilla, I.; Sanchez-Cano, A.; Ferreras, A.; Acha, J.; Pérez-García, D.; Ibañez-Alperte, J.; Abecia, E. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Objective: To evaluate the ability of short-wavelength automated perimetry (SWAP) for the detection of visual impairment in patients with type I diabetes without retinopathy or with minor retinal vascular changes.Design: Comparative cross-sectional study.Participants: 30 eyes of 30 healthy subjects and 73 eyes of 73 patients with type I diabetes mellitus were studied.Methods: Ophthalmic examination of diabetic patients showed no retinopathy or minimal changes (less than 5 microaneurisms in each eye) with no previous laser treatment. All patients were examined by means of the SWAP 24-2 strategy. Mean Deviation (MD) and Pattern Standard Deviation (PSD) were compared between both groups.Results: There were differences in the clusters of altered points between both groups (p=0.004). SWAP MD was lower in the diabetic group than in the controls (−2.89 dB vs. −0.20 dB, p<0.001). SWAP PSD also differed between both groups (2.50 dB in control group, 3.12 dB in the diabetic group, p=0.003). In the diabetic group, mean period from the onset of diabetes was 12.6±6.7 years and minimal vascular changes were observed in the retina of 18 eyes (24.7%), while 55 had no lesions (75.3%). No differences in SWAP changes were found between patients without and with minimal diabetic retinopathy.Conclusions: Retinal sensitivity assessed by SWAP is depressed in patients with type I diabetes regardless of the presence of retinal vascular changes.
Keywords: diabetes; retinopathy; microaneurisms; short-wavelength automated perimetry; visual field